Enhancing Solar Smartphone Charger Efficiency Through MPPT Technology - Yunus, Muhammad Hilman Hakimi; Saiman, Suhaimi (Evolution in Electrical and Electronic Engineering, 2024)
This work focuses on the comprehensive design and development of a solar-powered smartphone charger integrated with Maximum Power Point Tracking (MPPT) technology. The research encompasses the study of Photovoltaic (PV) systems to understand their principles and characteristics. Additionally, an exploration of buck converter methodologies is undertaken to efficiently regulate the output voltage from the PV system to meet smartphone charging requirements. Calculations involving power, voltage, current, load, selection of the capacitor, inductor for PV system buck converter are crucial components of the design process. The research extends to the meticulous selection of components, considering their specifications, availability, and suitability for the intended application. MATLAB is employed for simulation purposes, enabling the assessment of the proposed system's performance under varying conditions. The work progresses to the hardware configuration, where the theoretical aspects are translated into a practical setup. The combination of these research components aims to provide a holistic understanding of the solar smartphone charger design, from theoretical principles to practical implementation, contributing to the advancement of sustainable and efficient charging solutions.